O. O. Potebnia about sources of studying the history of East Slavic languages - Глущенко, Володимир Андрійович; Рябініна, Ірина Миколаївна; Тищенко, Катерина Анатоліївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article stated that O. O. Potebnia made a significant contribution to solving the problem sources study of East Slavic languages. Analyzed a number of capital works of scientists that entered the golden fund of domestic linguistics. It is proved that the priority source for the history of language in O. O. Potebnia’s works were modern dialects; material ancient written records were classified as among the most important auxiliary sources. The thesis on the priority of modern dialectal data as the source of the study of the history of language O. O. Potebnia argued the very practice of his linguistic research. The ignorance of this source was assessed by the scientist as a significant disadvantage of his contemporary studies from the history of language. As for ancient written monuments, they, as O. O. Potebnia believed, have significant disadvantages, which cannot be called the first priority source for studying the history of language. The significance of these abstracts should be weighed down. We foresee the prospects of further exploration in the frontal in-depth study of O. O. Potebnia’s research devoted to the history of East Slavic languages at various levels.